2023
DOI: 10.1088/2058-6272/ac92cd
|View full text |Cite
|
Sign up to set email alerts
|

Multi-point discharge model: study on corona discharge of double-ended needle in large space

Abstract: Corona discharge, as a common means to obtain non-equilibrium plasma, can generally obtain high concentration plasma by increasing discharge points to meet production needs. However, the existing numerical simulation models used to study multi-point corona discharge are all calculations of small-scale space models, which cannot obtain the distribution characteristics of plasma in large space. Based on our previous research, this paper proposes a hybrid model for studying the distribution of multi-point dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Pattern formation has also been observed to occur for glow discharges interfacing with a metal anode as reported in handful of publications [15][16][17][18]. Several of these observations were for different plasma operation conditions as typically used for glow discharges with liquid electrodes.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pattern formation has also been observed to occur for glow discharges interfacing with a metal anode as reported in handful of publications [15][16][17][18]. Several of these observations were for different plasma operation conditions as typically used for glow discharges with liquid electrodes.…”
Section: Introductionmentioning
confidence: 64%
“…Several of these observations were for different plasma operation conditions as typically used for glow discharges with liquid electrodes. This includes reduced pressure [16,18] and very high currents of the order of amperes [17]. Only Shirai et al [15] reported pattern formation on a metal anode with similar operation conditions as used for glow discharges with liquid electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have simulated the corona discharge of nanoelectrodes in the micro-discharge gap in ionization sensors [2,[25][26][27], they cannot be applied to scenes requiring large discharge gaps (centimeter-level) such as gas purification and electronic equipment cooling. In our previous study, we proposed a method to solve the corona discharge model with a large discharge gap based on the hydrodynamic model and ion migration model [28][29][30][31]. This method effectively solves the problem of difficult convergence of corona discharge models with large computational domains (much larger than the electrode size).…”
Section: Introductionmentioning
confidence: 99%